Conceptual principles of formation of the system of rational agricultural land use - Dorosh, Y.; Barvinskyi, A.; Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2022)
The article analyses the current state of agricultural land use in Ukraine, which is characterized by extremely high levels of ploughing of agricultural lands, violation of scientifically substantiated crop rotation, and hence significant anthropogenic pressure on the soil, which in turn increases the intensification of degradation.The conceptual bases of formation of the system of rational agricultural land use in the conditions of transformation of land relations are substantiated. It is proved that such systems should be formed at the national, regional and local levels based on the principles of environmental friendliness, adaptability, biogenicity, variability, etc. using a landscape approach to the organization of agricultural enterprises. To ensure the conservation of soil resources and zero level of degradation processes, the main block of such systems, their basis should be soil protection and reclamation of the territory.Only land management should be considered as the main mechanism for the formation of a system of rational agricultural land use, and therefore the process of its formation at the national level should be carried out through the development and implementation of the National Land Use and Protection Program; at the regional level - through the development and implementation of regional land use and protection programs; at the local level – through the development and implementation of relevant land management projects.Keywords: agricultural land use, system, degradation processes, soil protection and reclamation landscaping.